Răspuns :
a + b + c = 375
b = a + 15 => a = b-15
b=c-18 => c = b+18
inlocuim: b-15+b+b+18=375; 3b+3=375; 3b=372; b = 124
c = b+18; c= 124+18; c = 142;
a = b-15; a = 124-15; a = 109
b = a + 15 => a = b-15
b=c-18 => c = b+18
inlocuim: b-15+b+b+18=375; 3b+3=375; 3b=372; b = 124
c = b+18; c= 124+18; c = 142;
a = b-15; a = 124-15; a = 109
a+b+c=375
b=a+15=>a=b-15
b=c-18=>c=b+18
b-15+b+b+18=375
3b=375-18+15
b=372:3
b=124
a=124-15=109
c=124+18=142
Asa este !
b=a+15=>a=b-15
b=c-18=>c=b+18
b-15+b+b+18=375
3b=375-18+15
b=372:3
b=124
a=124-15=109
c=124+18=142
Asa este !